Rainbows, mirages, and sundogs : the sky as a source of wonder - Gallant, Roy A. (London : Collier Macmillan, 1987)
Discusses and explains visual phenomena seen in the sky, primarily interactions of light and atmosphere such as rainbows, mirages, the twinkling of stars, the blue color of the sky, and the Northern Lights.
Includes index.
Horn Book.
The Science Teacher (N.S.T.A.).
5.4
5.4
5-8.
Keywords: Meteorological optics -- Juvenile literature; Meteorological optics; Meteorological optics